PENGARUH JUMLAH SUDU TERHADAP KINERJA TURBIN SAVONIUS TIPE DRAG PADA ALIRAN AIR DALAM PIPA - Jamaldi, Agus; Purwono, Arif Hidayat; Andriyansyah, Deni; Raharjo, Emanuel Budi (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
The concept of clean and renewable energy is currently a focus developed continuously. One of the abundant sources of clean and renewable energy is water. A water turbine is a mechanism to generate electrical energy by utilizing the water flow. Pico or nano hydro turbines produce electrical energy by taking advantage of the flow of water that rotates the shaft of the electric generator. This experimental study aims to analyze the effect of differences in the number of blades on a Horizontal axis drag-type Savonius turbine mounted of water flow in a vertical pipe. The variations of blades number used in the study are 3, 4, 6, 8, 10, and 12. The potential energy of the water is kept constant with a constant head of 2 meters. Four main parameters used as a benchmark for the performance of water turbines are rotor rotation, voltage, current and electrical power generated. The results showed that the rotor rotation, voltage, current, and generated electrical power decreased as the number of blades used increased. The water turbine of 3 blades produces the best performance compared to the other one. The magnitude of the rotor rotation, voltage, current, and electrical power generated is 846 rpm, 15.28 volts, 0.61 amperes, and 9.38 Watts, respectively.